China's Rational Calculation (Cost-Benefit) in Mediating the Normalization of Iran and Saudi Arabia Relations - Purba, Yehezkiel; Wibowo, Prihandono (LPPM Institut Pendidikan Nusantara Global, 2025)
Saudi Arabia and Iran are two countries that serve as powerhouses in the Middle East region. They severed diplomatic relations following the vandalism and arson of the Saudi Arabian embassy in Iran in 2016. The attack was a response by the Iranian public to the Saudi government's execution of Sheikh Nimr al-Nimr. In 2023, Iran and Saudi Arabia normalized diplomatic relations through several agreements, including the reopening of embassies and the reactivation of security and trade agreements, facilitated by China in Beijing. This study focuses on the reasons why China chose to act as a mediator in the normalization process between Saudi Arabia and Iran. The research uses a qualitative-explanatory approach through the perspective of the Rational Actor Model. It is found that China's decision to act as a mediator was a rational choice that yielded more benefits through a cost-benefit analysis. These benefits include securing energy supplies, ensuring a stable investment climate, reducing the risk of cooperation failures, and opening up opportunities for further collaboration. On the other hand, the costs borne by China include the diplomatic burden of having to succeed in this mediation and the future expectations placed on China to maintain these benefits. An alternative policy is bilateral hedging, which also presents potential advantages such as saving diplomatic resources and fostering short-term trade relations. However, it also comes with drawbacks such as energy supply disruptions, damage to the investment climate, and the loss of strategic momentum and trust for China.